Polyethyleneimine impregnated alginate capsule as a high capacity sorbent for the recovery of monovalent and trivalent gold - Yub Raj Dangi (Nature Portfolio, 2021)
Abstract For the first time, a polyethyleneimine-impregnated alginate capsule (PEIIAC) with a high adsorption capacity is developed for the recovery of monovalent and trivalent gold from an acidic solution. The strategy results in a new type of adsorbent, polyethyleneimine impregnated alginate capsule (PEIIAC) with a core–shell structure having a large number of amine groups as cationic binding site, facilitating maximum uptake of anionic auric chloride. The maximum uptake of PEIIAC was 3078 and 929 mg/g for Au (III) and Au (I), respectively, are recordable compared to other reported adsorbents to date. The as-prepared material was executed to check the sorption efficacy for Au (III) and Au (I) in the pH range of 1–12. With an increment in pH, the uptake capacity for Au (III) increased, while the uptake capacity for Au (I) decreased. The FTIR, XRD, and XPS studies revealed that the gold adsorption mechanism includes ionic interactions and reduction, wherein the amine, hydroxyl, and carboxyl groups are involved. The capsule showed a higher adsorption efficiency than other reported sorbents, making the material applicable in acidic solutions for the recovery of Au (I) and Au (III).